Customer Relationship Management (CRM) implementation strategy to increase customer loyalty (case study at Bamboo Distro in Dlingo, Bantul Regency, DIY) - Dhea Amanda Putry; Uswatun Chasanah (Priviet Social Sciences Journal, 2026)
This study aims to analyze the implementation strategy of Customer Relationship Management (CRM) in enhancing customer loyalty at Distro Bamboo, a bamboo craft SME in Dlingo, Bantul, Yogyakarta. Amid intensifying competition in the craft industry and customers' tendency to switch brands, managing customer relationships has become crucial. This research employs a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews with six informants selected using purposive and snowball sampling techniques, consisting of the owner, two employees, and three customers, complemented by direct observation and documentation. Data analysis utilized the interactive model proposed by Miles, Huberman, and Saldana (2014). The findings reveal that CRM implementation at Distro Bamboo is conducted organically through a personal approach, manifested in four main strategies: (1) customer identification based on direct interaction and memory; (2) personal interaction through responsive two-way communication in-store and on social media; (3) empathetic and solution-oriented after-sales service; and (4) value creation through quality products and order flexibility. Consequently, these strategies successfully build trust, encourage repeat purchases, and generate customer advocacy (word of mouth). Customer loyalty is driven not by low prices but by the quality of relationships and products. The main obstacle is the lack of systematic technology and data recording, which simultaneously presents an opportunity for developing a simple CRM system in the future. This study concludes that personal and emotionally-based CRM proves effective and relevant for local craft SMEs.